Extracting Neural Oscillation Signatures of Laser-Induced Nociception in Pain-Related Regions in Rats - Li, Xuezhu; Zhao, Zifang; Ma, Jun; Cui, Shuang; Yi, Ming; Guo, Huailian; Wan, You (Frontiers in Neural Circuits, 2017)
Previous studies have shown that multiple brain regions are involved in pain perception and pain-related neural processes by forming a functionally bound pain network. It is still unclear how these pain-related brain areas actively work together to generate the experience of pain. To get a better insight into pain network, we implanted electrodes in four pain-related areas of rats including the anterior cingulate cortex (ACC), orbitofrontal cortex (OFC), primary somatosensory cortex (S1) and periaqueductal gray (PAG). Patterns of oscillations under noxious laser stimulation were analyzed and a high-dimension feature space were constructed based on local field potentials (LFPs). Generalized linear models (GLM) were trained to classify recorded LFPs under noxious laser stimulations and innoxious laser stimulations. We found a general power decrease in alpha and beta bands and power increase in gamma band in the recorded areas under noxious stimulation. After noxious laser stimulation, LFP power and correlation changes of the four brain areas had a uniform pattern across 13 recorded rats. With GLM classifiers, noxious laser trials were distinguished from the innoxious laser trials with high accuracy (89%) using high-dimensional LFP features. This work forms a foundation for further experiments to determine what aspects of the noxious stimuli (e.g. sensory, motor or affective processes) drive distinct neural activity across the pain network.